Evaluating the impact of virtualization characteristics on SaaS adoption - Tomás, Sara (2022)
Tomás, S., Thomas, M., & Oliveira, T. (2018). Evaluating the impact of virtualization characteristics on SaaS adoption. Enterprise Information Systems, 12(3), 259-278. https://doi.org/10.1080/17517575.2017.1355484